MENTORING FOR ECE ADMINISTRATORS AND EDUCATORS IN PRESCHOOL SERVICE QUALITY ASSURANCE TO SUPPORT THE ONE-YEAR COMPULSORY EARLY CHILDHOOD EDUCATION PROGRAM - Mutoharoh Mutoharoh; ⁠Miftahudin ⁠Miftahudin; ⁠Minhatul Maarif; ⁠Busron ⁠Busron; ⁠Siti Arofa; Jaruwat Songmuang (Yayasan Education and Social Center, 2025)
This community engagement program aimed to enhance the capacity of early childhood education (ECE) administrators and teachers in implementing quality assurance systems for preschool services, thereby supporting the national One-Year Compulsory Early Childhood Education initiative. The program was conducted over one month in September 2025 at Salsabilla Hotel, Anyer, employing a participatory approach that integrated socialization sessions, structured training, hands-on practice, mentoring, group discussions, and evaluation. Participants consisted of ECE administrators and educators directly involved in delivering early childhood education services. The findings indicate a significant improvement in participants’ understanding of quality assurance concepts, their ability to develop quality assurance documentation, and their skills in designing context-specific service improvement programs. Intensive mentoring further facilitated the development of participants’ commitment to fostering a quality culture through internal evaluation and continuous improvement practices. Beyond individual competency development, the program produced actionable follow-up plans to be implemented within each participating ECE institution, ensuring program sustainability. The high level of participant engagement and enthusiasm suggests that practice-based mentoring is an effective model for strengthening human resource capacity in early childhood education settings. Overall, this initiative contributes meaningfully to improving the quality of preschool services and supports the effective implementation of the One-Year Compulsory ECE policy through strengthened institutional governance and enhanced professional competencies among educators and administrators